Synthesis of some 1,3-diazepine -4,7-diones derivatives (part 2) - Hussein, F. A.; Mahrnoud, M. J.; Tawfiq, M. T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
1,3-0xazepine-4)-diones were  prepared by c.ondensation of NÂcinnamylideneareneamines with maleic anhydride,  phthalic;; anhydride,and  3-nitrophthalic  anhydride.  The  oxazepjne::; were  reacted  withprimary aromatic  amine  to give the corresponding  1 ,3--diazepine-4,7- diones.